The Role of Pesantren Education in Developing Students’ Entrepreneurial Character - Maya Apriyana; Wildan Munawar; Anas Alhifni; Lise Purnamasari; R. Siti Pupu Fauziyah; Abraham Yazdi Martin; Nova Monaya; Imam Abdul Aziz; Imam Kurniawan (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Entrepreneurial character development is a vital aspect of preparing students for self-reliance and economic contribution, particularly within Islamic boarding schools (pesantren) that integrate religious and life skills education. This study aims to examine the influence of the educational role and curriculum of Islamic boarding schools on students’ entrepreneurial character. Employing a quantitative descriptive approach, data were collected through a survey using structured questionnaires distributed to 35 pesantren managers as respondents. The findings reveal that the educational role of pesantren has a significant influence on students’ entrepreneurial development, as indicated by a test value of 95.413 > 1.96 and a p-value of 0.00 < 0.05. In contrast, the curriculum does not show a significant influence, with a test value of 1.252 < 1.96 and a p-value of 0.219 > 0.05. These results suggest that while structured learning content may not directly impact entrepreneurial outcomes, the broader educational environment and role modelling within pesantren play a critical role in shaping entrepreneurial character. This study underscores the importance of enhancing the educational dynamics and practical engagement in Islamic boarding schools to foster entrepreneurship as a core value in Islamic education.